Empowering biomedical learners to navigate FDA regulatory processes and entrepreneurship with a novel interdisciplinary training approach - Cola, Philip A.; Mangosh, Tawna L. (Frontiers in Medicine, 2025)
For rising professionals to meet the needs of contemporary healthcare and biomedical innovation, educators must develop new teaching and learning approaches. Specifically, biomedical innovations are significantly influenced by the FDA’s regulatory framework, requiring professionals to be equipped with regulatory science knowledge, entrepreneurial skills, and interdisciplinary training. However, biomedical education often fails to integrate these skills in an environment that mimics the interdisciplinary setting required for translational science, leaving learners unprepared for unique challenges in practice. This study details an FDA Regulation and Entrepreneurship curriculum at Case Western Reserve University and its affiliated community, leveraging a novel approach for biomedical education. Focused on preparing biomedical professionals to navigate FDA regulatory processes and innovative entrepreneurship endeavors, the curriculum is built upon five core principles: integrating multiple disciplines, ensuring real world applicability, developing a systems thinking approach, incorporating ethical considerations, and fostering a collaborative and experiential learning environment. These principles are supported by a flexible course format, targeted learning objectives, team-based learning sessions, experiential learning opportunities, a diverse participant population, and an interdisciplinary team of faculty and experts. High participant engagement and broad representation across fields over the curriculum’s three-year lifespan to date affirm its relevance and value with participants representing the fields of basic science, medicine, law, business, and engineering. The flexible course format, team-based learning, and experiential learning proved instrumental in enhancing engagement, reinforcing practical learning outcomes, and supporting personalized learning goals. The flexible course format further aligns with professional needs of participants, providing a model for other institutions navigating similar challenges in biomedical education. In conclusion, participant feedback demonstrated the value of the interdisciplinary and transdisciplinary training approach in promoting knowledge retention and skill development in complex medical, business management and legal contexts. Moving forward, targeted outreach and flexible engagement options will be necessary to expand the curricular reach and diverse participant population. The success of the curriculum suggests promising implications for similar approaches aimed at empowering biomedical professionals with essential regulatory, entrepreneurial and interdisciplinary competencies, ultimately advancing translational science and improving healthcare outcomes.